2011
DOI: 10.1007/s10658-011-9835-x
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of silicon in the banana-Cylindrocladium spathiphylli pathosystem

Abstract: Silicon (Si) is known to reduce the incidence of pathogens on many plants. Little information is available on the potential positive effects of Si on the susceptibility of banana (Musa acuminata) to pathogens. Root-rot fungi of the genus Cylindrocladium have been reported, along with endoparasitic nematodes, to be the causal agent of toppling disease and severe yield loss. The objective of this study was to determine the effects of Si supply on Cylindrocladium spathiphylli infection on banana. Plantlets inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 29 publications
0
13
0
3
Order By: Relevance
“…There have been a few reports of Si-induced resistance against bacterial pathogens, with the most notable report being Si-induced resistance in tomatoes against Ralstonia solanacearum (Diogo & Wydra, 2007;Kurabachew & Wydra, 2014). The beneficial role of Si application for banana has been demonstrated only against fungal diseases such as black sigatoka and root-rot caused by Mycosphaerella fijiensis and Cylindrocladium spathiphylli, respectively (Vermeire et al, 2011;Kablan et al, 2012). In addition, Fortunato et al (2012) showed that supplying Si to banana plants had a great potential to reduce the intensity of fusarium wilt.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a few reports of Si-induced resistance against bacterial pathogens, with the most notable report being Si-induced resistance in tomatoes against Ralstonia solanacearum (Diogo & Wydra, 2007;Kurabachew & Wydra, 2014). The beneficial role of Si application for banana has been demonstrated only against fungal diseases such as black sigatoka and root-rot caused by Mycosphaerella fijiensis and Cylindrocladium spathiphylli, respectively (Vermeire et al, 2011;Kablan et al, 2012). In addition, Fortunato et al (2012) showed that supplying Si to banana plants had a great potential to reduce the intensity of fusarium wilt.…”
Section: Introductionmentioning
confidence: 99%
“…For black sigatoka, caused by Mycosphaerella fijiensis, disease progress was faster and the symptoms were more severe in plants grown in the absence of Si, and high Si concentration in the leaves of plants resulted in reduced disease symptoms (27). In the roots of banana plants grown on a ferralsol amended with 2 mM Si, Si produced a reduction of ≈50% of the necrosis caused by Cylindrocladium spathiphylli, in addition to improving the plant growth (53).…”
mentioning
confidence: 99%
“…Using the image analysis program WinRHIZO, Vermeire et al (2011) exhibited that root-rot fungi Cylindrocladium spathiphylli infection in banana could be mitigated. The Si amendment also alleviated growth reduction caused by the pathogen.…”
Section: Banana Root Rotmentioning
confidence: 99%